2020
DOI: 10.1186/s13731-020-00121-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth of micro and small scale enterprises and its driving factors: empirical evidence from entrepreneurs in emerging region of Ethiopia

Abstract: Purpose The purpose of this study was to examine micro and small scale enterprises’ growth determinants operating in Benishangul-Gumuz Regional State of Ethiopia as emerging region. Design/methodology/approach The study adopted an explanatory research design with arrangement of primary data collection via a cross-sectional survey questionnaire followed by mixed research approach. The sample of this study was 220 enterprises determined by Yamane’s formula and selected using proportional stratified random sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 6 publications
1
49
0
Order By: Relevance
“…Evidently, business operating in premises allotted by government agencies had better chance of success compared to those set up in privately rented premises (Meressa, 2020). Moreover, a research conducted by Doris (2016) indicated that availability of land is very important for the success and sustainable growth of entrepreneurs because it creates access to resource and the necessary markets.…”
Section: Land Ownershipmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidently, business operating in premises allotted by government agencies had better chance of success compared to those set up in privately rented premises (Meressa, 2020). Moreover, a research conducted by Doris (2016) indicated that availability of land is very important for the success and sustainable growth of entrepreneurs because it creates access to resource and the necessary markets.…”
Section: Land Ownershipmentioning
confidence: 99%
“…Firms can have forward linkage with customers or other sellers and backward linkage with their raw material suppliers to get the needed materials to produce goods or services (Meressa, 2020). This is to mean that the absence or low supply of raw materials may increase the cost of production and bring other drawbacks like stagnation, low quality of products, and poor performance among others (Nasri & Muhammad, 2018).…”
Section: Access To Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors such as Mbugua et al (2013) and Meressa (2020) highlight that the growth of micro and small companies is directly linked to the sustainable development of underdeveloped economies. As stated by Meressa (2020), many researches sought to identify the variables that are widely used as determining factors in the growth process of companies.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Extensive evidence shows that the performance of women-owned micro and small enterprises (here after called as MSEs) are played pivotal roles for the development of a nation (Shakeel, Yaokuang, & Gohar, 2020)and the well-being of societies by creating jobs, wealth, and innovations (Mozumdar, Velde, & Omta, 2020). In Ethiopia, the importance of enterprises owned by women entrepreneur is noticed on different documents like industrial policy, MSEs development strategy, and the growth and transformation plans I and II to accelerate growth and reduce poverty (Meressa, 2020). Despite this, both the growth and performance of women owned MSEs remain a concern, although women entrepreneurship has gained popularity in the country with a growing number of women to start and run their own business (Awoke, 2019).…”
Section: Introductionmentioning
confidence: 99%